Genetic variation of Dacrycarpus imbricatus in Bromo Tengger Semeru National Park, East Java Based on trnL (UAA) Intron Region - Rahadiantoro, Apriyono; Hakim, Luchman; Arumingtyas, Estri Laras (Journal of Tropical Life Science, 2013)
The conservation of Jamuju Dacrycarpus imbricatus (Blume) de Laub. in Java Island has been considered important. One of the the limitation of such program is related to the viability data on the genetic diversity of species target. The aim of study was to determine genetic variation of D. imbricatus in Bromo Tengger Semeru Park, East Java based on trnL (UAA) intron region. DNA sample was collected from several D. imbricatus seedling population in Bromo Tengger Semeru National Park (BTSNP) in East Java. DNA was isolated and amplified using PCR. Genetic variation was estimated using trnL (UAA) intron sequences. This study confirm that D. imbricatus in Bromo Tengger Semeru has low genetic diversity. Based on the phylogenetic tree, D. imbricatus population from Bromo Tengger Semeru Park is closely related to D. imbricatus from Sabah-Malaysia and Hainan-China with 100 % similarity value. These data implies that population and habitat management of D. imbricatus in Bromo Tengger Semeru should be designed to enhance the population survival in the future.